Pharmaceutical Innovations: Superior Position of the USA and Weaknesses of German Research - Andreas Eckert; Wolfgang Maennig (Wirtschaftsdienst)
Abstract The innovative strength of research performance is often measured in terms of inputs such as research funds or outputs such as patent applications. We present a novel indicator of pharmaceutical innovativeness that focuses on global medical breakthroughs and associated patents. According to this indicator, US companies account for 55 % of global medical breakthroughs from 2010 to 2019, and their German competitors account for about 9 %. In terms of underlying anchor patents, the dominance of the US is even larger, at 62 %, while only 7 % of anchor patents come from Germany. US universities hold 3.8 % of all anchor patents; German universities hold none. The weakness of German universities cannot be compensated by German non-university research institutes.